A Case of a Laryngeal MALT Lymphoma in a Patient with a History of Gastric MALT. (18th January 2015) - Ashamalla, Mark; Teng, Marita S.; Brody, Joshua; Demicco, Elizabeth; Parikh, Rahul; Dharmarajan, Kavita; Bakst, Richard L.
Abstract : We are reporting a case of a 62-year-old African American woman with a history of gastric MALT lymphoma successfully treated with radiation who presented with a laryngeal MALT lymphoma 4 years after her original diagnosis. She received definitive radiation with a complete response. The case presented is unique for the rare presentation of a MALT lymphoma in the larynx, especially in light of the patient's previously treated gastric MALT lymphoma years ago.